Strengthening the Understanding of Pancasila as the State Foundation to Achieve National Goals - Susilawati N; Sultoni Sultoni; Bambang Niko Pasla (Badan Pengembangan Sumber Daya Manusia (BPSDM) Provinsi Jambi, 2021)
The basis of the state for a nation is very important as the goal of living as a nation and state. Indonesia has a state basis called Pancasila. In today's era, the noble values ​​of Pancasila have begun to fade and are practiced by citizens. Therefore, this paper describes the understanding of Pancasila as the purpose of life for the State. This paper is a collection of various books as a reference for citizens in fulfilling their independence. The discussion can be concluded that as the basis of the state, Pancasila acts as a source of all sources of state law and a source of value for the entire Indonesian nation. As the basis of the state, Pancasila is an important guideline in regulating the administration of the state, a source of inspiration, motivation, a source of law, and also the moral ideals of a country, and is a source for the preparation of the constitution in the Indonesian state. The ideals of the state law of the Republic of Indonesia in the four main ideas of the 1945 Constitution are essentially the same as Pancasila, namely God and Humanity, Unity State, Social Justice, and People's Sovereignty. Pancasila is the basis of the state of the Republic of Indonesia, therefore Pancasila is the source of all sources of state law of the Republic of Indonesia. The objectives of the State of Indonesia are stated in the fourth paragraph of the Preamble to the 1945 Constitution of Indonesia, namely: 1) Protecting every nation and the entire homeland of Indonesia: 2) Promoting public welfare. 3) To educate the nation's life, and 4) to Participate in carrying out a world order based on eternal peace and social justice.